BIMBINGAN KARIR DAN KEMANDIRIAN ANAK - Gusnimar, G; Amelia, Dina Nadira (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2018)
Career guidance is part of a comprehensive guidance and counseling program. Because directing children’s development in their lives includes very large dimensions, both at school and outside of school. Optimizing children's development through career guidance programs means ensuring that children have a broad understanding of the social roles that they can choose in the future, including interests, talents and jobs.Keywords: Career Guidance, and Children's Independence